IMPLEMENTATION GUIDANCE SERVICES GROUP TO OVERCOME INTROVERTED PERSONALITY - Khairul Amri; Dian Hasfera (Ristekdik : Jurnal Bimbingan dan Konseling, 2019)
Abstract: The study was based on concerns about the personality of the students in the school environment, especially regarding introvert (closed). The research goal is to overcome the introverted personalities of students in SMK Negeri 1 Padangsidimpuan through Guidance Services Group. The method used is a pre-experimental research with the shape of The One Group Pretest - Post Test Design. With a sample of experimental class is class XI Administration 1 as many as 10 students were 5 girls and 5 boys, so as the total sample of 10 students. Tutoring Services Group dilakukakan three meetings and one-time meeting information services, namely in the first meeting perform pretest and posttest perform all treatments. Data were analyzed using the Wilcoxon rank test signesd and Kolmogorov Smirnov 2 with the help SPSS version 20.00. From the results of operations to be carried, a decline in student introverted personalities are quite large, especially the second and third meetings. The findings in the experimental group there is a significant drop between the results of the posttest. to test the hypothesis used by the formula Wilcoxon signed rank test using SPSS version 20 o'clock Wilcoxon test was used to analyze the results of observations of the two data are different or not. On average variable introverted personalities of 142.6000 (posttest experiment) this looks very significant difference. The conclusion of this study the data processing, shows that the implementation of group counseling services can overcome introvert personalities. It is recommended for teachers to approach through group counseling, especially guidance to help shape the personality of students, both in learning, implementation and evaluation of learning. For further research, is expected to make a research on the introverted personalities through other methods